EPIDEMIOLOGY OF DROWNING CASES IN SOUTH-WESTERN PART OF MAHARASHTRA – AN AUTOPSY BASED FOURTEEN YEARS RETROSPECTIVE STUDY (Journal of Forensic Medicine & Toxicology, 2024)
Drowning is a significant public health issue and is the third leading cause of unintentional injury death worldwide. The easy accessibility and minimal restriction on entry into water bodies are the most common causes of drowning in India. Even though Maharashtra accounts for the maximum number of deaths from drowning has been conducted in the South-Western part of Maharashtra. The aim of the study was to analyze the epidemiology of drowning deaths among all medico legal cases brought for autopsy to a tertiary care center in the South-Western part of Maharashtra. This was a cross sectional retrospective study of medico legal autopsy cases conducted during the period of 2009 - 2022, in which the cause of death was asphyxia due to ante-mortem drowning. Amongst 3363 autopsies, drowning was identified as the cause of death in 154 (4.58%) cases. There was a higher occurrence of drowning among male, with a ratio of 2.3:1. The majority of these deaths occurred in individuals aged 21-30 years (24.7%). Unmarried individuals accounted for the largest percentage of drowning deaths (45%). Most bodies were recovered from running water (72.1%), and the manner of death was unknown in the majority of cases (51.94%). Deaths due to drowning commonly occurred during the summer season (March to June) (49.3%) and decomposition was often observed (31.8%). Stomach content (Wydler’s sign) and pulmonary edema were the commonest finding during autopsies (88.3% and 80.5%, respectively). Accidental death was the most common manner of death in known cases, which can be averted by studying the epidemiology of cases and planning prevention strategies for it.
Keywords: Drowning; Asphyxia; Accidental death; Suicide; Preventive strategy